Yield loss from plant parasitic nematodes in East African highland banan (Musa spp. AAA) - Speijer, P.R.; Kajumba, C. (International Society for Horticultural Science, 2000)
East African Highland bananas (Musa spp., AAA) also known by their vernacular name ‘matooke', are a major staple food for the densely populated high elevation regions of Eastern and Central Africa. Banana production, however, is declining due to increased pest and disease pressure. Nematodes are considered to be a major constraint. An experiment was established at the East and Southern Africa Regional Centre of the International Institute of Tropical Agriculture at Sendusu (Uganda) to assess the yield loss caused by nematodes to East African Highland banana. Sendusu, at an elevation of 1128 m, is representative of the lower Musa production zones in Uganda. The major nematode species affecting Musa at this elevation are Radopholus similis and Helicotylenchus multicinctus. The production of a plant crop of East African highland banana, established with hot water disinfested planting material, was 51% higher compared to a crop established with nematode infested material. Bunch weight was significantly higher (P < 0.001) in plots planted with disinfested propagules than in those plots planted with nematode infested material. Owing to vigorous growth and lower plant toppling (P < 0.01), more bunches were harvested (P < 0.01) in the non-infested plots compared to the plots established with infested planting material. Root and rhizome damage and R. similis and H. multicinctus density were significantly lower in roots of suckers detached from harvested plants (P < 0.001) established with disinfected material compared to suckers detached from nematode infested material.